Accountability of Temporary Land Deed Official Not Included as Defendants in Deed Revocation Rulings: Study of Verdict Number 601/Pdt.G/2020/Pa.Tnk. - Nilna Firkhana Soraya; Sukarmi; Patricia Audrey Ruslijanto (Jurnal Ilmu Kenotariatan, 2025)
This study examines the role of the Temporary Land Deed Official (PPATS) in the issuance of legally defective deeds. The case, as adjudicated in Verdict Number 601/Pdt.G/2020/PA.Tnk, indicates that the PPATS was neither designated as a Co-Defendant nor held materially liable to the disputing parties. In the court's consideration, the judge reasoned that the PPATS was not directly implicated in the case since the Grant Deed (Akta Hibah) was not annulled, but rather the "grant" itself. Nevertheless, the judge ruled that the Grant Deed was legally defective, lacked binding legal force, and was declared null and void by operation of law. Consequently, the verdict contains a formal defect (plurium litis consortium) due to the absence of a complete set of necessary parties in the lawsuit, which, in principle, should have resulted in the dismissal of the case. This study addresses two main issues: (1) the legal consequences of a Grant Deed that is null and void by operation of law, and (2) the actions that the PPATS can take to maintain their integrity and professional accountability in the event of such a declaration. This research employs a normative legal approach, utilizing the theory of legal responsibility as its analytical framework.